VESTIBULAR MIGRAINE-CASE REPORT - Babunovska Marija; Arsovska, Anita; Kuzmanovski Igor; Cvetkovska Emilija; Boshkovski Bojan; Gјorcheva, Irena; Mitrevska Velkov Jasmina; Isjanovski, Igor (My University, 2016)
Background: Vestibular migraine is a term that is included in the classification of the International Headache Society (ICH) 2016. Diagnostic criteria for vestibular migraine include: A) at least 5 episodes that fulfill criteria C and D; B) current or past history of migraine without or with aura; C) vestibular symptoms with moderate to severe intensity, lasting from 5 minutes till 72 hours; D) At least 50% of the episodes have one of the following migrenous characteristics:1. a) unilateral localization b) pulsatile quality c) moderate or severe intensity d) worsening after routine physical activity 2. Photophobia and phonophobia 3. Visual aura. Approximately 40% of the migraine patients have vestibular migraine. It is also important to emphasize that headache is not always present. Case presentation: We present 32 year old female patient who complained of attacks of vertigo, caused by movement of the head, lasting 10 minutes, several times a week that was sometimes accompanied by unilateral headache, with pulsatile quality and nausea. Otherwise, her physical and neurological examination was normal.The following investigations were made: laboratory blood analysis, nuclear magnetic resonance (NMR) of the brain and cervical spine, color duplex sonography of the carotid and vertebral arteries and audiovestibular testing- all with normal findings. A suspicion for vestibular migraine was raised and the patient was recommended therapy with SSRI, management of stress and appropriate life-style modification. Her control examination after one month showed reduction of her symptoms.Conclusion:Young adult women (20-40 years) have increased risk for vestibular migraine. Differential diagnosis includes benign positional vertigo, Menier disease, transient ischemic attack in the vertebra-basilar system and vestibular nerve irritation. Treatment includes Ca channels blockers, SSRI, Clonazepam, Beta blockers, stress management, exercise and life-style modification.
Keywords: vestibular, migraine